2015
DOI: 10.5194/hess-19-4257-2015
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the natural hydrology of the San Francisco Bay–Delta watershed

Abstract: Abstract.We evaluated the impact of landscape changes on the amount of delta outflow reaching San Francisco Bay. The natural landscape was reconstructed and water balances were used to estimate the long-term annual average delta outflow that would have occurred under natural landscape conditions if the climate from 1922 to 2009 were to repeat itself. These outflows are referred to as natural delta outflows and are the first published estimate of natural delta outflow. These natural delta outflows were then com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Under predevelopment conditions, winter and spring flows spilled over the banks of the Sacramento and San Joaquin rivers, filling low-lying basins adjacent to these rivers and attenuating peak flows. Under preproject conditions, man-made levees largely isolated these rivers from their floodplains and other wetlands (thereby decreasing evapotranspiration) and conveyed their flows more directly to the Delta, resulting in higher peak flows consistent with the findings of Fox et al (2015) and Howes et al (2015). Under contemporary conditions, both river levees and floodcontrol projects are present, and the major reservoirs diminish seasonal flow variability as did the natural floodplain.…”
Section: Delta Outflowmentioning
confidence: 54%
See 2 more Smart Citations
“…Under predevelopment conditions, winter and spring flows spilled over the banks of the Sacramento and San Joaquin rivers, filling low-lying basins adjacent to these rivers and attenuating peak flows. Under preproject conditions, man-made levees largely isolated these rivers from their floodplains and other wetlands (thereby decreasing evapotranspiration) and conveyed their flows more directly to the Delta, resulting in higher peak flows consistent with the findings of Fox et al (2015) and Howes et al (2015). Under contemporary conditions, both river levees and floodcontrol projects are present, and the major reservoirs diminish seasonal flow variability as did the natural floodplain.…”
Section: Delta Outflowmentioning
confidence: 54%
“…The seasonal flooding pattern of the pre-development watershed supported vast inland marshes located in natural flood basins along major rivers (Alexander et al 1874;Hall 1887;Garone 2011;Fox et al 2015), while lush riparian forests existed on natural river levees (Katibah 1984), and vast swaths of grasslands interwoven with vernal pools and savannas with immense valley oaks extended from the floodplains to the oak-and pine-covered foothills (Burcham 1957;Dutzi 1978;Holland 1978). At lower elevations, permanent wetlands were supported by a shallow groundwater table fed by seasonal overflows from the rivers.…”
Section: Geographic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…If reasonable proxies for historical topographic maps can be generated, then improved hydrological modeling-in particular two-dimensional flood routing to dynamically allocate water across flood basins and improve treatment of backwater effects during peak flood conditions-would provide a more nuanced treatment of flood extents and persistence than the simple hypsometric curve approach adopted here. It is useful to note that the bounding cases adopted in this study, although adopted from topographic reasoning, span uncertainty bounds on natural inflow partitioning to ET developed in previous studies, as shown by the comparisons to the Fox et al (2015) and Department of Water Resources, Bay Delta Office (2016) estimates in Figure 7. This reinforces our finding that even disparate landscapes, with their broadly variable channel capacities, levee heights, and potential for watershed storage can converge to replicate modern stream flows, making clear the imperative for additional, quantitative historical hydrologic data.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have addressed the history of change in flow in the San Francisco Delta, including efforts that focus on understanding the "natural" flow regime prevalent up to the mideighteenth century (Department of Water Resources, Bay Delta Office, 2016; Fox et al, 2015), hindcasts of flow and sediment yield during the 1850-1922 period based on analysis of tide gauge and river stage data in the San Francisco Bay and Delta (Moftakhari et al, 2013(Moftakhari et al, , 2015, and several studies that address the trends in flow and salinity during the instrumented period post-1922 (Enright & Culberson, 2009;Fox et al, 1990;Hutton et al, 2015Hutton et al, , 2017aHutton et al, , 2017bKnowles, 2002). The studies are broadly consistent and paint a picture of ongoing hydrologic change.…”
Section: Introductionmentioning
confidence: 99%